2004
DOI: 10.1200/jco.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Heparin, Therapy With Dalteparin, and Survival in Advanced Cancer: The Fragmin Advanced Malignancy Outcome Study (FAMOUS)

Abstract: Dalteparin administration did not significantly improve 1-year survival rates in patients with advanced malignancy. However, the observed improved survival in a subgroup of patients with a better prognosis suggests a potential modifying effect of dalteparin on tumor biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
404
1
18

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(442 citation statements)
references
References 26 publications
19
404
1
18
Order By: Relevance
“…These data extend previous observations that have implicated antimetastatic effects for heparin and HLGAGs in animal model systems (21)(22)(23)(24)(25)(26). Clinical studies have also indicated that heparin and HLGAGs may prolong survival of patients with cancer with solid tumors (3)(4)(5).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These data extend previous observations that have implicated antimetastatic effects for heparin and HLGAGs in animal model systems (21)(22)(23)(24)(25)(26). Clinical studies have also indicated that heparin and HLGAGs may prolong survival of patients with cancer with solid tumors (3)(4)(5).…”
Section: Discussionsupporting
confidence: 76%
“…Highly sulfated heparan sulfate glycosaminoglycans, such as heparin, are commonly used to prevent venous thromboembolism, which is a common complication in patients with cancer as well. Heparin and heparin-like glycosaminoglycans (HLGAGs) have also been shown to prolong survival of patients with cancer, suggesting an antimetastatic effect for these compounds (3)(4)(5). The applicability of heparin in cancer therapy is limited because of its strong anticoagulant activity, but HLGAGs with less undesired effects on blood coagulation have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, there has been increasing clinical evidence that anticoagulants have antitumour effects reducing the risk of cancer in patients with VTE and improving survival in patients with advanced malignancy (Zacharski et al, 1981;Schulman and Lindmarker, 2000;Kakkar et al, 2004). Cancer patients with VTE are at increased risk of second malignancies, but further work is needed before specific guidelines for their management would be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…This finding strongly indicates that inhibition of P-selectin is one of the main cancer inhibitory activities of heparin [91]. Based on the encouraging observations with heparin treatment evaluated in retrospective studies, several recent prospective clinical trials have been performed to study this phenomenon [92][93][94][95]. The promising results from the clinical studies, primarily in earlier stage patients together with the experimental evidence suggests that heparin treatment directly affect the metastasis rather than by simple inhibition of coagulation [35].…”
Section: Platelets As Therapeutic Targets For Anti-cancer Therapiesmentioning
confidence: 99%